2021
DOI: 10.3390/agriculture11010059
|View full text |Cite
|
Sign up to set email alerts
|

Key Competencies of Agricultural Managers in the Acute Stage of the COVID-19 Crisis

Abstract: The acute phase of the COVID-19 crisis exacerbated the need for managerial skills of agricultural managers, provoked another wave of discussion on content of managerial competencies in times of crisis, and revealed a significant research gap. The main goal of our study is to identify the impact of competencies of agricultural crisis managers on the performance of employees in the acute phase of the crisis, when the performance was influenced by their subjective perception and evaluation of their working condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…As it is demonstrated, contemporary scientific activities within the scope of the pandemic's black swan are focused on actual issues of dealing with this socio-economic phenomenon. Neither is their fragmentation in favor of establishing prospective future competitive advantage [15]. In accordance with what was mentioned above, the main aim of the article is to identify changes in intrinsic motivation sources of employees caused by the impact of the COVID-19 pandemic, and to discuss prospective modifications to the already formulated patterns of internal marketing communication.…”
Section: Literature Reviewmentioning
confidence: 84%
“…As it is demonstrated, contemporary scientific activities within the scope of the pandemic's black swan are focused on actual issues of dealing with this socio-economic phenomenon. Neither is their fragmentation in favor of establishing prospective future competitive advantage [15]. In accordance with what was mentioned above, the main aim of the article is to identify changes in intrinsic motivation sources of employees caused by the impact of the COVID-19 pandemic, and to discuss prospective modifications to the already formulated patterns of internal marketing communication.…”
Section: Literature Reviewmentioning
confidence: 84%
“…They considered it necessary to have information about how to start a company, how to organize a possible team or how to make quality products. These aspects were also specified in a previous study, in which it was concluded that the performance of employees in a period of crisis can be influenced by competent crisis management and can increase support for teamwork [71].…”
Section: Opinions Of Employers Teachers and Students Regarding The Sk...mentioning
confidence: 98%
“…Covid-19 had an unprecedented impact on society, the economy, and the environment (Bapuji et al, 2020;Bansal, 2020). It represented a health crisis, sensitively perceived by every citizen because it threatens human health (Jankelová and Misun, 2021), but at the same time, it caused a deep economic crisis with long-term consequences (Bodziany et al, 2021;Baker et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%